A Dual-Harmonic Pole-Changing Motor with Split Permanent Magnet Pole - Du, Yi; Zhou, Jiayan; He, Zhuofan; Sun, Yandong; Kong, Ming (Energies (Basel), 2022)
This paper proposes a dual-harmonic pole-changing (PC) motor with split permanent magnet (PM) poles (DHPCM-SPMPs). By adopting a split PM pole structure, the amplitude of the third PM flux density is increased greatly. Therefore, when a PC winding is adopted to couple with the fundamental and third PM flux density components, respectively, the proposed motor can work as a PC PM motor to satisfy operating demands of electric tractors. The design and effect of the proposed split PM pole structure is introduced first. The winding topology is then designed according to the slot vector diagrams of the two PM flux density components, and the PC operation can be realized by electric switches. Aiming at a torque ratio design objective, the PM structure parameters can be determined based on mathematical derivation, and the speed-widening capability is proved based on the operation characteristic analysis. Finally, the electromagnetic performance of the DHPCM-SPMPs is investigated and compared by finite element analysis, which shows the high torque capability in eight-pole mode and the wide speed range in twenty-four-pole mode benefiting from the PC operation.